Kesalahan Bahasa dalam Penulisan Abstrak Skripsi Mahasiswa PBA - Niswatush Sholihah; Wakhidati Nurrokhmah Putri (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2023)
This research was motivated by the language errors found in the abstracts of the PBA students' thesis. These language errors can be broken down and classified by linguistic categories. By knowing more detailed errors, follow-up efforts can be made to minimize these errors. The purpose of this study was to determine the forms of language errors in the PBA student thesis abstracts. This research is a qualitative descriptive study. Methods of data collection by observation, and documentation. The results of the study found morphological errors in the form of isytiqaq errors and fi'il selection errors in terms of time, syntactic errors in the form of mismatches of na'at and man'ut, application errors the rule of 'adad ma'dud, misformation of tarkib idhafy, incompatibility of fi'il and fa'il, incompatibility of mubtada' and khobar, not adding the letter fa' to the answer to the condition "Amma", errors in the sign of i'rab, incompatibility of isim isyaroh and musyar ilaih, and errors in the use of dhomir, and semantic errors in the form of errors in the use of jar letters, inaccuracies in the choice of diction, and the literal translation of Indonesian into Arabic. This study focused on linguistic errors found in the abstracts of the PBA students' thesis from IAIN Kudus and IAIN Salatiga in 2021.